Jalan Swadaya Perumahan Bogor: Integrasi Desain Sirkulasi dan Resiliensi Iklim untuk Ruang Hidup Aktif - Agung Sugiarto (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
The rapid pace of housing development in Bogor has created a gap with the provision of formal infrastructure, which has encouraged the emergence of community-led self-help road initiatives. While capable of addressing urgent connectivity needs, these road formations often ignore essential design standards, particularly those related to circulation and environmental context. This study focuses on a specific challenge in Bogor, namely high rainfall ("force of nature"), which contributes to road degradation, causing flooding, and reducing user comfort. Adopting a descriptive qualitative method, this study analyzes the existing self-help access conditions through field observations and a literature review focusing on Water Sensitive Urban Design (WSUD) principles and circulation theory. Field findings confirm that the current design fails to manage surface runoff, resulting in low infiltration and the emergence of functional space conflicts (e.g., for parking and social activities). As a solution, this study proposes an integrated design demonstration that combines porous materials and micro-drainage to manage the force of nature, thereby improving circulation comfort and supporting active living for residents.